Stern-judging: A simple, successful norm which promotes cooperation under indirect reciprocity - Pacheco, Jorge M. (2017)
JMP acknowledges support from FCT, Portugal, and the Program for Evolutionary Dynamics at Harvard University. FCS acknowledges the support of COMP2SYS, a Marie Curie Early Stage Training Site, funded by the European Community through the HRM activity. FACCC was supported by project POCI/MAT/57546/2004.